2013
DOI: 10.5862/mce.41.4
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of turbulent flow velocity characteristics

Abstract: Magazine of Civil Engineering, №6, 2013Брянская Ю.В. Уточнение кинематических характеристик турбулентного течения Уточнение кинематических характеристик турбулентного течения К.т.н., профессор Ю.В. Брянская, ФБГОУ ВПО «Московский государственный строительный университет» Ключевые слова: течение в трубах; теория турбулентности; профиль скорости; параметр Кармана; гидравлическое сопротивление Полуэмпирическая теория турбулентности Прандтля -Никурадзе, которая позволила получить распределение скоростей, согласующ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Comparison of the formulas (15) and (16) showed that the Laplace formula corresponds quite accurately to the dependence (16) Using the dependence (17), it is true for wave perturbations having a length commensurate with the depth of the flow, the condition V k =С gives: The calculations according to (18) show that the critical Froude number is significantly less than 1 under wave disturbances, the length of which is less than 2πh.…”
Section: Methods and Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Comparison of the formulas (15) and (16) showed that the Laplace formula corresponds quite accurately to the dependence (16) Using the dependence (17), it is true for wave perturbations having a length commensurate with the depth of the flow, the condition V k =С gives: The calculations according to (18) show that the critical Froude number is significantly less than 1 under wave disturbances, the length of which is less than 2πh.…”
Section: Methods and Resultsmentioning
confidence: 93%
“…1). With this deviation, the depth of the flow changes towards a smaller or larger value of the conjugate depths corresponding to the specific energy of the cross section after the change [2,5,8,[15][16][17][18][19][20]. In this case, the water surface is either a bumpy, unstable, wave surface, or there is a hydraulic jump.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The purpose of the experiments was to provide special conditions for the liquid flow with a forced agitation of suspended substances in it by creating various structured relief surfaces on the tray inner surface. Herewith, a prospective model of the particle motion was considered not as their spontaneous drawing in the bottom part of the pipe, but as a spasmodic movement in the flow (without caking) [18]. In this case, the amount of the deposed sediments remains minimal regardless of the rates and the fillings of the pipeline.…”
Section: Methodsmentioning
confidence: 99%